Occurrence and antibiotic resistance of Campylobacter and Arcobacter spp. in dogs and cats - Goni, Mohammed Dauda (2014)
Campylobacter and Arcobacter are becoming more recognised because of their detection in a wide range of hosts and food of animal origin. Campylobacter is considered one of the most common causes while Arcobacter has emerged as a cause of gastro-enteritis in humans and both are of public health concern. They are gram negative, curved, spiral or S- shaped and are members of the order Campylobacterales, class Epsilon and phylum Proteobacteria. Several studies have been conducted in developed countries on their occurrence and characterisation in dogs and cats but such studies are lacking in most developing nations like Malaysia. Due to this present scenario, this study was conducted to determine the presence of Campylobacter and Arcobacter in dogs and cats and to also determine antibiotic resistance patterns of the isolates. The presence of these organisms was determined using conventional and molecular techniques. For Arcobacter, rectal and buccal swab samples were collected from owned dogs (40) and cats (40) presented to the University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM) and a private veterinary clinic within Kuala Lumpur, and stray dogs (61) and cats (46) from an animal shelter and Dewan Bandaraya Kuala Lumpur (DBKL) dog pound. Rectal swabs were also taken for the detection of Campylobacter in these animals. Suspected colonies of the two organisms were subcultured and subjected to biochemical tests which included catalase, oxidase, hippurate hydrolysis and indoxyl acetate hydrolysis tests. Multiplex polymerase chain reaction (mPCR) was employed for the confirmation of the suspected isolates and differentiation of species. Overall, the results showed carriage rates of 32.6% (15/46) and 12.5% (5/40) of Campylobacter in stray and client owned cats respectively, while Arcobacter was detected in 34.78% (16/46) and 45% (18/40) in stray and client owned cats respectively. In stray dogs, Campylobacter and Arcobacter were detected at 16.3% (10/61) and at 50% (31/61) respectively. Arcobacter butzleri was the only species that was isolated and © COPYRIGHT UPM ii Campylobacter upsaliensis (60%), C. helviticus (20%) and C. jejuni (11.4%) were the species of Campylobacter isolated. Risk factors for Campylobacter and Arcobacter infections in dogs and cats were determined through questionnaires filled by pet owners. Among the factors that were looked at included age, sex, breed category, single or multi-pet household, recent treatment with antibiotic, housing of the dogs and cats, source of drinking water, contact with other animals, consumption of raw meat and fish and place of residence of the owner. Factors found to significantly increase the risk for Arcobacter infections were multi-pets household type and source of drinking water in cats while none were significant in the case of dogs. None of the factors analyzed was significant in terms of the occurrence of Campylobacter in both dogs and cats. Antibiotic resistance pattern using minimum inhibitory concentration (M.I.C) and disc diffusion methods were carried out. Eighty nine (89) Arcobacter butzleri and 28 Campylobacter isolates were tested against 12 antibiotics using the disc diffusion method namely ciprofloxacin (Cip) 5µg; ampicillin (Amp), 10 µg; tetracycline (Te), 30 µg; erythromycin (E), 15 µg; gentamicin (CN), 10 µg; cefotaxime (CTX), 30 µg; penicillin G (P), µg; streptomycin (S), µg; nalidixic acid (NA), µg; enrofloxacin (Enr), µg; amoxicillin/clavulanic acid (AMC), µg and ceftazidine (CAZ), µg. Four antibiotics, namely ampicillin, tetracycline, erythromycin and ciprofloxacin were used against Campylobacter and Arcobacter butzleri isolates for the M.I.C. Overall, the isolates were found resistant to at least one antibiotic using both techniques. For Campylobacter isolates, the resistance to the antibiotics using the disc diffusion method was as follows: ciprofloxacin (17.8%), gentamycin (32.1%), cefotaxime (42.8%), penicillin G (53.5%), tetracycline (32.1%), ampicillin (42.8%), erythromycin (50%), streptomycin (42.8%), nalidixic acid (46.4%), amoxycillin/clavulanic acid (17.8%), ceftazidine (50%) and enrofloxacin (21.4%). Using the M.I.C.E. strip (Oxoid), Campylobacter and A. butzleri isolates showed exception in the resistance to ciprofloxacin. For Arcobacter isolates the resistance to antibiotics using the disc diffusion was as follows: ciprofloxacin (2.1%), gentamicin (63.1%), cefotaxime (69.4%), penicillin G and ampicillin (98.9%), tetracycline (33.6%), erythromycin (53.6%), streptomycin (85.2%), nalidixic acid (61.0%), amoxycillin/clavulanic acid (43.1% ), ceftazidine (3.6%) and enrofloxacin (31.5%). In comparison, the resistance rates between the disc diffusion and M.I.C. were not significantly different. The antibiotic resistance showed and 35 patterns for Campylobacter and Arcobacter isolates respectively. Campylobacter isolates were found resistant to nine (9) antibiotics while Arcobacter showed resistance to ten (10) antibiotics. Multi drug resistance (MDR) was reported among 50% and 78.9% of Campylobacter and Arcobacter isolates respectively. It can be concluded that the occurrence of Campylobacter and Arcobacter species in dogs and cats is of great public health significance as pets are in close contact with humans. Good management and controlling the population of stray dogs and cats are key factors in preventing the spread of Campylobacter and Arcobacter in these animal species. Antibiotic resistance in Campylobacter and Arcobacter not only increases the risk of treatment failure in both humans and animals but also spreads antibiotic resistance genes.